2012
DOI: 10.1682/jrrd.2001.04.0070
|View full text |Cite
|
Sign up to set email alerts
|

Participant perceptions of use of CyWee Z as adjunct to rehabilitation of upper-limb function following stroke

Abstract: Abstract-This article reports on the perceptions of 14 adults with chronic stroke who participated in a pilot study to determine the utility, acceptability, and potential efficacy of using an adapted CyWee Z handheld game controller to play a variety of computer games aimed at improving upper-limb function. Four qualitative in-depth interviews and two focus groups explored participant perceptions. Data were thematically analyzed with the general inductive approach. Participants enjoyed playing the computer gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 37 publications
4
27
1
1
Order By: Relevance
“…Moreover, the difficulties of the tasks of video games and virtual reality can be controlled and modulated rendering these tools [8] usable in clinical and home settings [2]. Benefits from video game-based therapy were initially demonstrated for upper-limb recovery [9], but, at present, the results on balance and mobility are inconclusive [1, 10]. In particular, little evidence is available in patients with residual disability and balance disturbances after the subacute phase of stroke [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the difficulties of the tasks of video games and virtual reality can be controlled and modulated rendering these tools [8] usable in clinical and home settings [2]. Benefits from video game-based therapy were initially demonstrated for upper-limb recovery [9], but, at present, the results on balance and mobility are inconclusive [1, 10]. In particular, little evidence is available in patients with residual disability and balance disturbances after the subacute phase of stroke [11].…”
Section: Introductionmentioning
confidence: 99%
“…(2326) Only a few studies, however, have investigated the individuals' actual experiences using such video game approaches. (27,28)…”
Section: Introductionmentioning
confidence: 99%
“…For example, Belchior et al suggested that older adults' immersion during VR-based games could be adjusted to their skill levels [52]. Hale et al reported that patients with stroke seemed to enjoy VR-based rehabilitation when they were equipped with suitable technology [21].…”
Section: Discussionmentioning
confidence: 99%
“…At present, only the perspectives of patients with neurological conditions regarding VR-based rehabilitation have been explored [16][17][18][19][20][21], whereas few studies have examined the perspectives of patients with musculoskeletal conditions regarding VR-based rehabilitation. Musculoskeletal conditions are the most common reason for long-term pain and physical disability, causing 54 percent of all long-term disability and 24 percent of all restricted activity days [22][23], and regular exercise participation is reported to be important for the treatment of these musculoskeletal conditions [24].…”
Section: Introductionmentioning
confidence: 99%